Optimalisasi Open Source Relational Database Menggunakan Metode Replication dan Metode Cluster - Arief Ginanjar; Mokhamad Hendayun; Wahyu Purnama Sari (Jurnal ICT: Information Communication & Technology, 2023)
Information technology are developed very fast in the present days. Along with the development of time, the amount of data and users will also increase which results in process of accessed and process workload will become slower. The ability to provide fast retrieve information is highly demanded to be more efficient and effective at these time, hopefully no problems occur when the required data is to be access. To overcome this problem there are technologies called Cluster and Replication that can help ensure high service availability by utilizing several computer resources that work together. If there’s a server that experiences failure, the system will not be immediately disrupted because other servers will continue functioning and replace the task of main server. Cluster capabilities allow a database to stay alive for a long time. Replications are techniques to copy and distribute database and objects from one to another database and synchronise between them. And data consistency can be keepted. Testing results with clusters tend to be faster, and testing between double VMs and triple VMs looks superior to triple VMs so it can make new alternative of choice in implementing database programming